2008
DOI: 10.1366/000370208786822304
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis Modeling of Pulse-Laser Excited Photothermal Deflection (Mirage Effect) from Aerosols

Abstract: A finite element analysis method for numerical modeling of the photothermal deflection spectroscopy of aerosols is presented. The models simulate pulse-laser excited photothermal deflection from aerosols collected on a plane surface substrate in air medium. The influence of the aerosol and substrate properties on the transient photothermal deflection signal is examined. We have previously obtained experimental results for photothermal deflection spectrometry of aerosols deposited onto a plate from an impactor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(29 reference statements)
1
7
0
1
Order By: Relevance
“…The paper shows invariance of transient photothermal deflection signal on shape, number of particles, and inter-particle spacing. 27 The results also indicate that the signal magnitude is relatively stable with substrate thermal properties especially with high absorbance particles. This paper shows that experimental results are in good agreement with the numerical results.…”
Section: Introductionmentioning
confidence: 82%
“…The paper shows invariance of transient photothermal deflection signal on shape, number of particles, and inter-particle spacing. 27 The results also indicate that the signal magnitude is relatively stable with substrate thermal properties especially with high absorbance particles. This paper shows that experimental results are in good agreement with the numerical results.…”
Section: Introductionmentioning
confidence: 82%
“…PDS is very promising for sorption detection, and provides very sensitive determination of various analytes . Iron(II) chelate with ferrozine has been selectively detected by sorption preconcentration, with limit of detection being 8 × 10 −12 and limit of quantification being 2.5 × 10 −11 mol cm −2 …”
Section: Outlooks For Photothermal Characterization Of Cellulose and mentioning
confidence: 99%
“…[91][92][93] Iron(II) chelate with ferrozine has been selectively detected by sorption preconcentration, with limit of detection being 8 3 10 À12 and limit of quantification being 2.5 3 10 À11 mol cm À2 . [94] It is shown that the due regard to the changes in the chemistry at the trace level increases both the sensitivity and the selectivity of PT determination of these species compared to conventional spectrophotometry. [68,70,95,96] As a whole, the advantages of thermal-lens spectrometry over spectrophotometry from the viewpoint of procedure development and complex characterization are summarized below in Figure 10.…”
Section: Direct Use Of Agroindustrial Productsmentioning
confidence: 99%
“…8 Esto impone una cota máxima sobre el radio que deben tener las partículas para obtener un intercambio de calor eficiente a una dada frecuencia de excitación. Acorde a esto y a (1) se puede inferir que la señal FA depende no solo de la masa iluminada, a través de  sino del tamaño de las partículas depositadas, a partir de f 7,17 .…”
Section: Figura 1: Las Partículas Depositadas En El Sustrato Absorbenunclassified